Epistemological Format ofPedagogical Science and Evidence-based Pedagogy - A. V. Korzhuev; N. N. Antonova (Высшее образование в России)
The article addresses the problem of epistemological basis of pedagogy and its research methods. This is particularly relevant in the light of the formation of theoretical framework in pedagogy. The following topical themes are discussed in the article: a) inductive, hypothetico-deductive and abductive reasoning in pedagogy, b) causal explanations of pedagogical phenomena, c) argumentation of pedagogical conclusions and consequences, including empirical, theoretical and contextual types of argumentation. The authors briefly touch upon the logical interpretation of “norm” and “evaluation” in pedagogy. The problems related to pedagogical theory constructing are identified including incompleteness of abductive model, insufficient evidence of all types of pedagogical argumentation and causal interpretation, and lack of clarity of the category “measure”.